Probabilistic Assessment of Domino Effect Triggered by Fire: Implementation in Quantitative Risk Assessment - G. Landucci; G. Antonioni; A. Tugnoli; V. Cozzani (Chemical Engineering Transactions, 2012)
The present study was aimed at the quantitative assessment of domino effect triggered by fires. A recent methodology based on simplified correlations for the determination of vessel resistance to fire exposure was applied to estimate the damage probability of equipment exposed to fires. The analysis was aimed at evidencing the quantitative contribution due to the domino escalation to a risk profile of industrial facilities. A case study was defined for the application of the methodology obtaining a significant risk increment due to the implementation of domino effects triggered by fire in a Quantitative Risk Assessment (QRA) framework.